Rancang Bangun Alat Penyangrai (Roasting) Kopi Otomatis Menggunakan Metode Fuzzy - Rahmawati, Diana; Nanda Muhendra Data; Haryanto; Miftachul Ulum (J-Eltrik, 2021)
One of the processes in making coffee is the roasting process, this process is the processing of raw coffee beans into ripe coffee beans. Each roasting has a different way, both traditional and modern. As for the traditional method, from the process carried out the results of the ripeness of the coffee beans obtained are still not evenly distributed so that it is not as desired and the use of tools in the roasting process is less efficient. Meanwhile, in the modern way, the tools used must be appropriate based on the characteristics so that if they are not used according to the rules, the results of the roasting are not appropriate. From these problems, an efficient roasting tool will be made to produce quality coffee beans maturity. The working system of this tool uses a coffee weight input that uses the fuzzy logic method to get the ripening time of the coffee beans and then this tool will work by rotating the coffee bean stirrer inside the roasting tube using a dc motor (direct current) based on the time obtained. Heating uses a heating element, with an automatic control system based on the detected temperature sensor and will then control the heater to the desired temperature. If the temperature is still less than the set point then heating will remain on, whereas if the temperature exceeds the set point then heating will be turned off. So that a stable heating temperature is obtained. From the tests that have been done, this tool can ripen 3 types of coffee beans, namely robusta, arabica, and liberica. This tool has 3 variants of ripeness of coffee beans, including light roast, medium roast and dark roast.